2013
DOI: 10.3998/ark.5550190.p008.131
|View full text |Cite
|
Sign up to set email alerts
|

A review of recent progress (2002-2012) on the biological activities of pyrazoles

Abstract: Dedicated to Professor Rosa M. Claramunt on the occasion of her 65 th anniversary AbstractIn this review, we report the structures of 243 pyrazoles with their corresponding biological activities. All of them are represented around the common structure of the pyrazole ring even in those cases where the heterocycle is only a minor part of the molecule. The classification we have used is based on chemical structure considerations and not in terms of the therapeutic area which is the more common approach. Some gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 99 publications
0
33
0
Order By: Relevance
“…Abdel-Maksoud et al have demonstrated antitumoral activity of several compounds with a pyrazole and sulfonamide moieties [19]; antibacterial and antifungal activity of pyrazole was demonstrated by Chowdary et al [20]. Pyrazoles also showed good activity as monoamine oxidase inhibitors, antidepressant and anticonvulsant agents [21], as BRAF inhibitors [22] and DNA gyrase inhibitors [23] and present antileishmanial, anti-inflammatory, analgesic, antidiabetic and cannabinoid activity; cyclin-dependent kinase and tissue-nonspecific alkaline phosphatase inhibitory activity and moderate antihepatotoxic activity, among others [9,11,[24][25][26][27][28][29]. In 2013, Prabhu et.…”
Section: Pyrazolesmentioning
confidence: 97%
“…Abdel-Maksoud et al have demonstrated antitumoral activity of several compounds with a pyrazole and sulfonamide moieties [19]; antibacterial and antifungal activity of pyrazole was demonstrated by Chowdary et al [20]. Pyrazoles also showed good activity as monoamine oxidase inhibitors, antidepressant and anticonvulsant agents [21], as BRAF inhibitors [22] and DNA gyrase inhibitors [23] and present antileishmanial, anti-inflammatory, analgesic, antidiabetic and cannabinoid activity; cyclin-dependent kinase and tissue-nonspecific alkaline phosphatase inhibitory activity and moderate antihepatotoxic activity, among others [9,11,[24][25][26][27][28][29]. In 2013, Prabhu et.…”
Section: Pyrazolesmentioning
confidence: 97%
“…Pyrazole derivatives are also useful in the treatment of obesity and CNS disorders including Alzheimer's and Parkinson's disease. [1][2][3][4] Among the anticancer drugs, pyrazole or indazole derivatives like Celecoxib, anthrapyrazoles (piroxantrone, losoxantrone), and Axitinib Magnesium ions, Mg 2+ , participate in many biochemical processes including these involved in cancerogenesis like proliferation, angiogenesis and apoptosis. 7,8 The role of magnesium in cancerogenesis is, however, not clearly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazole and its derivatives attract the attention of the chemical community mainly on account of the wide spectrum of their pharmacological activities, [1][2][3][4][5][6] including antibacterial, 7 antidepressant, 8 antiinflammatory, 9 antitumor, 10 etc. They are widely used as agrochemicals.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 They are also applied in the design of complexes with unusual magnetic properties. 26,27 In the search for novel pyazoles as building blocks for the synthesis of biologically active and technologically useful substances, [1][2][3][4][5][6] the development of new methods for the preparation of functionalized pyrazoles and the synthesis of new pyrazole derivatives present an urgent challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation